The Social Functioning of Knowledge and Science in the Philosophy of Paul Feyerabend – Ideologies, Interactions, and Cosmologies - Lampart, Jakub (Folia Philosophica, 2021)
In his article, Jakub Lampart addresses the social, cultural, and historical functions of various forms of knowledge (and of science in particular) as they can be reconstructed on the basis of the few descriptive remarks found in Paul Feyerabend’s works in the three periods of his scholarly career: moderate, transitional, and radical. Lampart interprets Feyerabend’s views on the relationship between knowledge and society as influenced by the following: the early concepts of Karl Popper (in the moderate period), some of the theses of Benjamin L. Whorf and the late Ludwig Wittgenstein (in the radical period). The article also contains: a) a juxtaposition of Feyerabend’s views with the theories of these thinkers; (b) an attempt to explain Feyerabend’s use of the term “ideology”; (c) a description of two trends characterizing different systems of knowledge: isolation and interaction; d) a description of the two types of ideal members of a given tradition: rationalists and pragmatists.